Demystifying computational thinking. (November 2017) - Shute, Valerie J.; Sun, Chen; Asbell-Clarke, Jodi
Abstract: This paper examines the growing field of computational thinking (CT) in education. A review of the relevant literature shows a diversity in definitions, interventions, assessments, and models. After synthesizing various approaches used to develop the construct in K-16 settings, we have created the following working definition of CT: The conceptual foundation required to solve problems effectively and efficiently (i.e., algorithmically, with or without the assistance of computers) with solutions that are reusable in different contexts. This definition highlights that CT is primarily a way of thinking and acting, which can be exhibited through the use particular skills, which then can become the basis for performance-based assessments of CT skills. Based on the literature, we categorized CT into six main facets: decomposition, abstraction, algorithm design, debugging, iteration, and generalization. This paper shows examples of CT definitions, interventions, assessments, and models across a variety of disciplines, with a call for more extensive research in this area. Highlights: Review of current CT literature shows no consensus definition or model of CT. We propose a definition and model of CT to inform instruction and assessment. Our CT model can be used across disciplines and educational settings. We illustrate how the model is being adapted for assessment in a CT learning game.